1976
DOI: 10.1002/app.1976.070200908
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfone hollow fibers. I. Spinning and properties

Abstract: SynopsisThe development of porous polysulfone hollow fibers and the spinning process used are discussed. An analysis is given of the spinning parameters which determine fiber mechanical properties and permeability. Hollow fibers were prepared which display high modulus and high tensile strength. These fibers can withstand hydraulic pressures of more than 1000 psi. They can thus serve as supports for dense, ultrathin membrane coatings, useful in high-pressure reverse osmosis and ultrafiltration processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(69 citation statements)
references
References 2 publications
4
65
0
Order By: Relevance
“…Any effect on the performance of the membranes was not reported. The diameter of the hollow fiber depends on the take-off rate and on the extrusion rate of the polymer solution as was published by Cabasso et al [3]. Espenan et al [2] found that the diameter of the fiber decreases when the airgap becomes longer or when the flow rate of the polymer solution decreases.…”
Section: Membrane Formation By Spinning Hollow Fibers From the Systemmentioning
confidence: 72%
See 2 more Smart Citations
“…Any effect on the performance of the membranes was not reported. The diameter of the hollow fiber depends on the take-off rate and on the extrusion rate of the polymer solution as was published by Cabasso et al [3]. Espenan et al [2] found that the diameter of the fiber decreases when the airgap becomes longer or when the flow rate of the polymer solution decreases.…”
Section: Membrane Formation By Spinning Hollow Fibers From the Systemmentioning
confidence: 72%
“…Even so the number of fundamental contributions to this subject is limited [1][2][3][4][5][6]. Much knowledge about the spinning of porous hollow fiber membranes has been described in patents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table I shows the molecular weights, polydispersities, compositions, and mechanical properties a1. [19][20][21] Table I. Samples B and C have the crystal size of 1.29 and 0.81 nm, respectively, due to their lower acrylonitrile content.…”
Section: Hollow Fibermentioning
confidence: 99%
“…Despite its usefulness and adaptability to different membrane separation processes [1][2][3][4][5][6][7][8][9][10], the fundamental study on the hollow fibre is very scarce in the literature. The reason may be that flat-sheet membranes are relatively easy to prepare, and the fundamental principles underlying membrane formation and membrane transport are considered to be the same regardless of the membrane shape and membrane configuration.…”
Section: Introductionmentioning
confidence: 99%